TANTANGAN DAN POTENSI: IMPLEMENTASI RUANG GURU DAN TENAGA KEPENDIDIKAN (GTK) DI SEKOLAH MANDIRI BERUBAH - Indah Nurul Hazairin; Ajuzar Fiqhi; Muhammad Fadly Habibi; Ahmad Fikri; Muhammad Sanusi (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the implementation of the Ruang Guru dan Tenaga Kependidikan (GTK) platform within the Merdeka Curriculum at SMA Negeri 11 Muaro Jambi, which operates as an independent evolving (Mandiri Berubah) school. Methods: Employing a qualitative approach with a case study design, data were collected through direct observation, interviews, and document analysis. The research subjects were specifically selected using purposive sampling, focusing on tenth-grade teachers at SMA N 11 Muaro Jambi who actively utilize the Ruang GTK platform. Results: The findings indicate that the utilization of Ruang GTK still encounters various practical obstacles, primarily limited internet access, insufficient continuous training, and diverse teacher perceptions. Nevertheless, the study reveals the platform's significant potential in enhancing the overall quality of learning. These findings bear substantial implications for educational policy development, particularly concerning efforts to improve access to educational technology, foster teacher capacity building, and align the curriculum with digital platform integration. Novelty: This research provides a unique perspective by specifically uncovering the contextual challenges and practical opportunities of utilizing Ruang GTK at a public high school undergoing the Mandiri Berubah transitional phase, offering empirically grounded insights for localized educational policy adjustments.